(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
Technology has become a crucial component of modern education, revolutionizing traditional teaching methods and introducing innovative approaches to learning. This paper explores the advantages and disadvantages of integrating technology into the teaching process. Key benefits include increased interactivity, accessibility, personalized learning, and enhanced collaboration. However, challenges such as technical issues, cybersecurity risks, reduced face-to-face interaction, and difficulties in teacher adaptation must be addressed to optimize technology’s role in education. A balanced approach that combines digital tools with traditional methods can create a more effective and inclusive learning environment.